Maqashid Al-Syariah Implementation and Its Impact on SDGs Achievement in Lampung Baznas (2020–2024) - Nadia Emilia; M. Iqbal Fasa; Citra Etika (LPPM STIE Krakatau, 2026)
Purpose: This study aims to analyze the effect of Maqasid Al-Syariah on the achievement of Sustainable Development Goals (SDGs) at BAZNAS of Lampung Province during the period 2020–2024. Methodology: This study employed a quantitative approach using a survey method with questionnaires distributed to 98 mustahik respondents selected by purposive sampling. The data were analyzed using Structural Equation Modeling Partial Least Square (SEM-PLS) with SmartPLS software. Results: The results indicate that Maqasid Al-Syariah has a positive and significant effect on the achievement of SDGs, with a T-statistic value of 4.396 and a p-value of 0.000. The coefficient of determination shows that Maqasid Al-Syariah explains 34.1% of the variation in the SDGs achievement. Conclusions: The implementation of Maqasid Al-Syariah principles, including the protection of religion, life, intellect, lineage, and wealth, contributes significantly to sustainable development through zakat empowerment programs at BAZNAS Lampung Province. Limitations: This study is limited to one regional zakat institution, namely BAZNAS Lampung Province, with data collected only from mustahik respondents during 2020–2024. This may not fully represent the broader impact of zakat institutions in Indonesia’s economy. Contribution: This study provides empirical evidence linking classical Maqasid Al-Syariah principles to global SDGs within regional zakat institutions, offering zakat managers and policymakers insights for designing sustainable, inclusive development strategies, especially in post-pandemic economic recovery.